Analisis Faktor-Faktor Yang Mempengaruhi Nasabah Dalam Memilih Asuransi Syariah - Novi Atika Putri; Rini Apriyanti; Muhamad Aji Purwanto (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
Sharia insurance has become the main choice for most customers who want to secure their assets in a way that complies with Islamic principles. This research aims to analyze the factors that influence customers' decisions in choosing sharia insurance. The analytical method used is descriptive research with a quantitative approach, using a questionnaire as a data collection tool. The factors observed include trust, risk awareness, financial benefits, sharia compliance and service. The results of the analysis show that trust is the main factor influencing customers' decisions in choosing sharia insurance, followed by sharia compliance and service. Meanwhile, awareness of financial risks and benefits also has a significant influence, although not as big as other factors. The implication of this research is the importance of building customer trust through consistent application of sharia principles, improving service quality, and intensive education regarding the benefits and compliance of sharia in insurance. In conclusion, an in-depth understanding of these factors can help the sharia insurance industry in developing more effective marketing strategies and increasing customer trust and satisfaction